Implementation of Molecular Visualization Program for Chemistry Learning - Risnita Vicky Listyarini (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study aims to investigate the implementation of molecular visualization programs for improving students’ understanding of concepts in chemical bonding.  Chemistry learning in chemical bonding was conducted using molecular visualization program ACD/ChemSketch and Avogadro program. Several topics in chemical bonding include molecular geometry, polarity, bond angle, bond length, intermolecular forces and predicting boiling points. This study employs quasi-experimental research One Group Pretest – Posttest design. The subjects of this study were 46 students of undergraduate program in chemistry education department at Universitas Sanata Dharma.  This study use test (pretest and pretest) and questionnaire to assess students’ perception of implementation of ACD/ChemSketch and Avogadro in chemistry learning. Implementation of ACD/ChemSketch and Avogadro in chemistry learning of chemical bonding gave an effect on students’ understanding based on paired t-test (sig < 0.05) and Kruskal-Wallis (sig < 0.05) test. The percentage of students is 45% with the medium N-gain category and 65% with the high N-gain category for ACD/ChemSketch program. It is 38.46% with the medium N-gain category and 61.54% with the high N-gain category for Avogadro program. Students show positive response to the implementation of ACD/ChemSketch and Avogadro program regarding their understanding, motivation and prospective skill for becoming teachers. Molecular visualization program helps the students to understand the chemical bonding topic.